Hybrid PD and adaptive backstepping control for self-balancing two-wheel electric scooter - Anh, Ho Pham Huy; Son, Nguyen Ngoc (Journal of Computer Science and Cybernetics, 2014)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> This paper proposes a combination of adaptive self-balancing controller and the left and right turning PD controller for self-balancing two-wheel electric scooter (eScooter). An adaptive self-balancing controller is synthesized by the backstepping approach and the Lyapunov stability theory. The proposed adaptive controller allows the design of a feedback control that stabilizes self-balancing control of eScooter in the presence of uncertainty and perturbation. Additionally, the sensor signals are treated by Kalman filters and the CAN networks are applied to communication among modules of eScooter. Simulation and experimental results are shown to analyze and validate the performance of proposed controller. <!–[endif] –>